Effect of Mo on the morphology, microstructure and mechanical properties of NbTa0.5TiMox refractory high entropy alloy fabricated by laser powder bed fusion using elemental mixed powders. (February 2023) - Wang, Fei; Yuan, Tiechui; Li, Ruidi; Lin, Shiqi; Niu, Pengda; Cristino, Valentino
Abstract: The production of refractory metal pre-alloy powder is difficult and the related production cost is high. In this paper, NbTa0.5 TiMo x series refractory high entropy alloy was prepared by laser powder bed fusion (L-PBF) with elemental mixed powders. The effects of Mo content on the morphology, microstructure, hardness, density, and compression properties of the NbTa0.5 TiMo x alloy were studied. All NbTa0.5 TiMo x alloys fabricated by L-PBF present a single-phase BCC. Typical dendrites are formed within the grains and the elements are enriched in the dendrite trunk and inter-dendrite region from inside to outside depends on the melting point of the different materials. It was observed that the Mo content improves significantly the hardness and compressive strength of the alloy by solution strengthening. NbTa0.5 TiMo1.0 alloy has the highest yield strength (1609 MPa), but with reduced ductility, while NbTa0.5 TiMo x ( x ≤ 0.5) alloy has excellent ductility ( e > 80%) at room temperature. The increase in Mo content leads to the increase of cracks, pores and non-penetration defects, resulting in the loss of sustained strength & ductility and decrease in density. The results provide a basis for the design and preparation of ductile refractory high entropy alloys by L-PBF of elemental mixed powders. Graphical abstract: Unlabelled Image Highlights: The NbTa0.5 TiMo x alloy was fabricated by LPBF using elemental mixed powders. The alloy is a single β phase and typical dendrites are formed within the grains. Hardness and compressive strength increased with increasing Mo content. The novel alloy shows high-ductility ( e > 80%, when x ≤ 0.5).